Pengaruh Komisaris Independen, Komite Audit Independen, Pergantian Chief Executive Officer dan Struktur Kepemilikan Saham Publik Terhadap Return On Asset (Studi Empiris pada Perusahaan Properti dan Real Estate di Bursa Efek Indonesia) - Rakhmat Irwansyah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The purpose of this study to analyze empirically the extent of the influence of the four independent variables are independent directors, independent audit committees, CEO turnover and structure of public ownership of the dependent variable is the return on assets(ROA). The study used secondary data on the Indonesia Stock Exchange, with a population of 51 companies and is considered complete and met the study criteria were 38 sample companies. The sample selection is done by purposive sampling in the field of real estate property during the five year study period the year 2009-2013. Model data analysis used multiple regression analysis (multiple regression) either partially or simultaneously.The test results proved and concluded that the proportion of independent directors, independent audit committees, CEO turnover and structure of public ownership according f and t test and a positive significant effect on return on assets(ROA).